Study on bacteriological quality of Kunun aya (Tigernut juice) sold at Umaru Musa Yar’adua University (UMYU) campus, Katsina - Umar, ZD; Bashir, A; Raubilu, SA (International Journal of Environment, 2014)
The study was aimed at determining the Bacteriological quality of Kunun aya (Tigernut juice) which is one of the most regularly non-alcoholic drinks consumed within Umaru Musa Yar’adua University campus. Samples were collected and analyzed from different places at the University for the Enumeration of bacteria. Serial dilutions were carried out from the collected samples where a dilution factor of 10-5 was obtained for each sample. Total aerobic bacterial counts, total coliform counts and Salmonella-Shigella counts were determined from the samples using Pour Plate Technique. The results obtained shows high bacterial load as the total aerobic bacterial counts had a range of 2.2x104 - 1.4x106 cfu/ml. Total coliform counts had 8.2 x 102 - 6.1 x 104 cfu/ml while Salmonella-Shigella counts had 1.1 x 102 - 8.7 x 104 cfu/ml. The result shows high bacterial contamination of Kunun aya, which may be obtained from the poor hygienic preparation process. This could be the reason for its quick spoilage. Preserving the drink in very low temperature may reduce the chances for its early spoilage. DOI: http://dx.doi.org/10.3126/ije.v3i2.10518 International Journal of the Environment Vol.3(2) 2014: 87-97